Chemical kinetics of silver diammine fluoride in demineralization and remineralization solutions-an in vitro study - M. Kaur; P. Anderson; S. Shahid; F. S. L. Wong (Frontiers Media S.A., 2024)
IntroductionSilver Diammine Fluoride (SDF) is a clinical minimal intervention to manage dentin caries. Its chemistry in demineralization conditions has been investigated widely, but far less in remineralization conditions. The aim was to investigate and compare the chemical reactions when SDF is added to remineralization and demineralization solutions.Methods0.01 ml SDF (Riva Star) was added to deionized water (DW); demineralization (DS = pH4) and remineralization (RS = pH7.0) solutions. The time sequence of concentrations of NH4+, F−, and Ag+ were measured using ion selective electrodes (ISEs) every 2 min. The pH was also measured. Precipitates were characterized using x-ray Diffraction (XRD) and, 31P and 19F nuclear magnetic resonance spectroscopy (NMR).ResultsThe concentrations of NH4+ and Ag+ showed decreasing trends in DW (−0.12 and −0.08 mM/h respectively), and in DS (−1.06 and −0.5 mM/h respectively); with corresponding increase in F− concentration (0.04 and 0.7 mM/h respectively). However, in RS, NH4+ concentration showed little change (0.001 mM/h), and Ag+ and F− concentrations were negligible. XRD results showed that precipitates (in RS only) contained AgCl, and metallic Ag. NMR showed that fluorapatite/carbonated fluorapatite (FAP/CFAP) were formed. The pH increased after SDF addition in all three solutions.DiscussionSDF dissolved to release NH4+, F− and Ag + . In DW and DS, NH4+ combined with Ag+ to form diamminesilver, causing an increase of F− and pH. In RS, F− reacted with Ca2+ and (PO)43− to form FAP/CFAP, and Ag+ reacted with Cl− to form AgCl/Ag. These suggests why SDF is effective in managing dentin caries.